The Examination of Vocational High School Students' Integration Levels to Higher Education According to Various Variables - Özlem Bayrak; Tuncer Bülbül (Sakarya University, 2013)
This study is performed for the purpose of examining academic and social integration levels of Vocational High School students in terms on various variables at student's social life during higher education. The sample of the study composed of 460 students from four Vocational High School at Trakya University. For data collection tool Institutional Integration Scales (IIS), developed by Pascerella and Terenzini (1980) were used. The scales were adopted in Turkish by Tuna (2010).The data were analyzed by using descriptive statistics, t-test, ANOVA and LSD Test. Findings stated that, Vocational High School Participant Students' adaptation levels at sub-dimension of Institutional Integration Scales were ''Not Sure'. Findings indicated that students' academic and social integration levels did not significantly differ based on gender, but differed significantly based on family income level and types of school.